Boa Morte: Reclaiming Kali, reframing death. Issue 4 (5th December 2018) - Wallace, Beverly
Abstract: A reframing of an understanding of death using indigenous religious concepts rooted in an African and a Hindu religious worldview is suggested in this article. Using her personal experiences, the author suggests that reclaiming and reframing the concept of death in terms of freedom, as held by the Order of the Sisters of the Good Death in the Candomble religious community of Brazil; representing death in terms of "letting go of ego" as personified by the Hindu Goddess Kali; and seeing death as black and beautiful and of energy as Kali, might be helpful for African Americans. Noting that death and the accompanying hurt and pain of death might move one to action, the need for death rituals is also suggested as a way for the community to begin the healing process, to be reconnected and to be "re‐membered."